2019
DOI: 10.1111/jgh.14604
|View full text |Cite
|
Sign up to set email alerts
|

Post‐endoscopic retrograde cholangiopancreatography pancreatitis in patients with asymptomatic common bile duct stones

Abstract: Background and Aim For asymptomatic common bile duct (CBD) stones, removal by endoscopic retrograde cholangiopancreatography (ERCP) is recommended in available guidelines. However, few studies have reported the risk of post‐ERCP pancreatitis (PEP), which is the most common and serious ERCP‐related complication for asymptomatic CBD stones. We performed a propensity score matching analysis to examine the risk of PEP in therapeutic ERCP for asymptomatic CBD stones. Methods Information from medical databases of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 30 publications
3
38
0
1
Order By: Relevance
“…We used standardized mean difference (SMD), which is not influenced by sample size, to check the balance of matched samples between single‐ and two‐stage stone removal groups. Propensity‐matched samples with SMD <0.10 is desirable . In this study, SMD in almost all factors shown in Tables and was <0.10, and SMD in only a factor of pancreatic injection was 0.105.…”
Section: Methodsmentioning
confidence: 59%
“…We used standardized mean difference (SMD), which is not influenced by sample size, to check the balance of matched samples between single‐ and two‐stage stone removal groups. Propensity‐matched samples with SMD <0.10 is desirable . In this study, SMD in almost all factors shown in Tables and was <0.10, and SMD in only a factor of pancreatic injection was 0.105.…”
Section: Methodsmentioning
confidence: 59%
“…In our previous study, we performed a propensity-matched analysis including 949 symptomatic CBD patients and 164 asymptomatic CBD patients and revealed that the incidence of PEP was significantly higher in patients with asymptomatic CBD stones than in those with symptomatic CBD stones [24/164 (14.6%) vs 28/949 (3.0%), P < 0.001, odds ratio: 5.6]. In another propensity-matched analysis of 158 matched pairs, a similar result was obtained [24/158 (15.2%) vs 5/158 (3.2%), respectively, P < 0.001, odds ratio: 5.5][7]. These findings were corroborated by those of other retrospective studies[8,9].…”
Section: Introductionmentioning
confidence: 59%
“…Meanwhile, the risk of procedure-related complications, particularly PEP, should be considered when performing ERCP in patients with asymptomatic CBD stones. The overall incidence rate of ERCP for asymptomatic CBD stone was approximately 20% and the incidence rate of PEP was reportedly between 12.5% and 14.6%[7,8]. This high incidence rate of PEP in patients with asymptomatic CBD stones may be attributed to the presence of multiple patient- and procedure-related risk factors, such as normal serum bilirubin levels, non-dilated CBD, and difficult biliary cannulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations